"Get yer ya-yas out": aspects of Perth's Greek Australian youth culture from the 1950s to the 1970s - Yiannakis, John (Modern Greek Studies Australia and New Zealand Association, 2012)
By the mid 1950s there was a distinctive youth culture emerging in much of the western world. From its epicentre in the United States, it spread to Europe and beyond as the postwar economic boom took hold across the ‘first world’. In Australia it would manifest itself in ways similar to overseas: through film, literature, dress, music, and politics. Other factors would also affect how youth bonded during these years, for example, mobility, games and fads, and sport. In Western Australia, young Greek migrants and an ever increasing number of Greek-Australian youth were exposed to these local and global cultural forces. How did these two groups react to these influences? What, if any, elements of western youth culture impacted on them? More specifically for the purposes of this article, what role did sport play in any emerging Greek youth culture in Western Australia? What do Greek youth sporting activities tell us about community dynamics and relationships? Did participation in sport hasten or slow assimilation during this period? This article seeks to address some of these latter questions through an analysis of two major Perth youth organisations.